2005
DOI: 10.1007/s11055-005-0115-0
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Shock Induces Neuron Death in the Mouse Hippocampus: Correlation of Neurodegeneration with Convulsive Activity

Abstract: The relationship between convulsive activity evoked by repeated electric shocks and structural changes in the hippocampus of Balb/C mice was studied. Brains were fixed two and seven days after the completion of electric shocks, and sections were stained by the Nissl method and immunohistochemically for apop totic nuclei (the TUNEL method). In addition, the activity of caspase-3, the key enzyme of apoptosis, was measured in brain areas immediately after completion of electric shoeks. The number of neurons decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Naïve bone marrow-injected animals composed, together with medium-injected animals, the control group for the Iba1 quantification (CTRL). Differences between the groups were detected for three main regions of interest, Cx, Hp and SN based on evidence that these areas are involved in motor activity [25] and electroconvulsive seizure susceptibility [26-28]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Naïve bone marrow-injected animals composed, together with medium-injected animals, the control group for the Iba1 quantification (CTRL). Differences between the groups were detected for three main regions of interest, Cx, Hp and SN based on evidence that these areas are involved in motor activity [25] and electroconvulsive seizure susceptibility [26-28]. …”
Section: Resultsmentioning
confidence: 99%
“…Although the tonic component of seizure was protected in MES-BM animals, the stimulated groups (MES-S, MES-DC and MES-BM) presented clonic seizures, which may explain the absence of differences in these areas and consequently suggest their responsiveness to the clonic seizure. In the hippocampus, a structure that is susceptible to convulsive seizures [42,43], and that contains cells vulnerable to electroshock [26-28], transplantation of bone marrow cells in MES animals was able to raise the number of microglial cells. Concerning these data, we speculated whether the observed increase in Iba1 cells in the hippocampus was due to its role in generalized or focal seizures and/or by a direct participation on persisting clonic seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Zarubenko et al [75] have shown that repeated ECS causes neuronal death. On the other hand, a number of studies have shown that repeated ECS increases neurogenesis [7678].…”
Section: Discussionmentioning
confidence: 99%
“…Like ECS, pilocarpine‐induced status epilepticus also causes dramatic and prolonged increases in cell proliferation in the SGZ (Gray and Sundstrom,1998; Parent et al,1997). However, prolonged seizures can thus cause synaptic reorganization with sprouting, involving aberrant growth of neural networks including granular cell axons (so‐called mossy fibers) in the SGZ of the fascia dentate and sprouting of CA1 axons in the CA1 subfield (Gombos et al,1999; Smith and Dudek,2001; Zarubenko et al,2005; Zhang et al,1998). Antidepressant drugs also increase cell proliferation in the dentate gyrus (Malberg et al,2000).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, apoptotic cells increased only 10‐fold in the ECS groups. Prolonged continuous seizure activity, as seen in status epilepticus, triggers neuronal cell death in the brain regions through which the seizure propagates (Zarubenko et al,2005; Zhang et al,1998). No significant increase in apoptotic cells was observed after 20 ECSs in our study, whereas apoptosis may be induced following prolonged continuous seizure.…”
Section: Discussionmentioning
confidence: 99%